Isolation, immortalization, and characterization of rabbit cortical collecting duct cells which express AT(1) angiotensin II receptors. - Regnier, Laura R. J. (University of Ottawa (Canada), 1995)
Functions of angiotensin II (Ang II) in distal nephron are poorly understood. To study Ang II signalling in cortical collecting duct (CCD), CCD cells were immortalized by transfection with a plasmid encoding the large T antigen of SV40. Hormone-induced (10$\sp{-7}$ M) cAMP responses were characteristic of intact CCD: arginine vasopressin (AVP) and prostaglandin E$\sb2$ (PGE$\sb2)$ significantly stimulated cAMP production, while parathyroid hormone (PTH) and salmon calcitonin (sCT) had no effect. Scanning electron microscopy (SEM) revealed cells with apical microplicae characteristic of $\alpha$-intercalated cells ($\alpha$-IC): other cells had few blunt microvilli consistent with either principal cells (PC) or $\beta$-intercalated cells ($\beta$-IC). Approximately 27% of transfected cells bound the rabbit $\beta$-IC marker peanut lectin agglutinin. Antibodies directed against surface antigens of PC (mAb 703) and IC (mAb 503), immunolabelled up to 26% of cells. In transfected cells, a single class of Ang II receptors (K$\rm \sb{d}$ = 0.78 nM) was detected by radioligand binding, and AT$\sb{1}$ Ang II receptor mRNA was demonstrated by Northern analysis. Ang II (10$\sp{-7}$ M) inhibited AVP-stimulated cAMP production, and low concentrations of Ang II (10$\sp{-12}$ M) significantly increased phosphoinositide hydrolysis. Thus, we immortalized a rabbit CCD cell line that retains characteristic morphological and hormonal properties. These cells express AT$\sb{1}$ Ang II receptors linked to inhibition of cAMP formation and to activation of phospholipase C. Coupling of Ang II receptors to these pathways may modulate CCD transport and growth.
Keywords: Biology, Cell.